Perubahan Status Fisiologis dan Bobot Badan Sapi Bali Bibit yang Diantarpulaukan dari Pulau Lombok ke Kalimantan Barat - Lalu Muhammad Kasip; Lalu Wira Pribadi; Sulaiman Ngongu Depamede; A. Rai Somaning Asih; Ambius Anton (Jurnal Ilmu Dan Teknologi Peternakan Indonesia (JITPI) Indonesian Journal of Animal Science and Technology), 2016)
The aims of this study were to investigate the changes of physiology and body weight of Bali cattle heiferstransported from Lombok Island to West Kalimantan. This was a case study on effect of transportation by shipof Bali cattle heifers from the Lombok Island to West Kalimantan. Twenty Bali cattle heifers with the initialbody weight of 123.28±11.00 kg were observed in this study. Samples were determined using the purposivesampling of the total 378 cattle during transportation. Body temperature, respiratory, pulse, hemoglobin,hematocrit, blood glucose and body weight of the heifers were measured prior to transportation (T0) and aftertransportation (T1). The temperature and humidity of the environment in the ship during the transportationwere also noted. Data were analyzed by using descriptive analysis (Arithmetic means) and the differenceswere tested using T-Test. The results show that livestock transportation had some negative effects on theperformances of the heifers. The average of the ship paddock temperature and the humidity during thetransportation period were 28.83±0.860C and 72.57±4.08%, respectively. The physiological status of bodytemperature; pulse; respiratory and blood glucose concentrations increased (P>0.05) by 0.600C; 8.25time/min; 7.6 times/min and 8.7 mg/dL, respectively. Whilst, the hematocrit levels, hemoglobin concentrationand body weight of the heifers decreased significantly (P>0.05) by 2.73%; 0.90 g/dL; and 21.23 kg/head,respectively. The high decrease of the heifers’ body weight changes (17.22%) was suspected to be due to lackof feed and water intakes during transportation. It is suggested that the heifers should have enough feed andwater consumption during tranportation for reducing stress.